Association between the infections of Trichomonas vaginalis and uterine cervical human papillomavirus: a meta-analysis. (31st December 2023) - Mei, Xuefang; Zhang, Rui; Li, Dongxian; Xie, Xianghuan; Yao, Yi; Gao, Minghui; Zhao, Linfei; Zhu, Shengyun; Tian, Xiaowei; Yang, Zhenke; Wang, Shuai; Zhang, Zhenchao
Abstract: Trichomonas vaginalis (TV) may have an impact on other reproductive tract infections. Studies on the connection between the infection of TV and human papillomavirus (HPV) have been inconsistent. We performed a systematic review of the relevant articles through keywords that satisfy the criteria and filtered the articles according to the inclusion and exclusion criteria. A total of 16 eligible studies were screened for the meta-analysis, involving a total of 150, 605 women. RevMan 5.4 software was used for meta-analysis of the selected literatures. The results showed that the papers included in this study had good homogeneity and no significant publication bias was found in the current analysis. The pooled estimates using a fixed-effects model showed that TV was more prevalent in HPV-infected women than in non-infected women [odds ratio (OR): 1.51, 95% confidence interval (CI): 1.29–1.75]; In turn, HPV was more widespread in TV-infected women than in uninfected women (OR: 3.62, 95% CI: 2.71–4.85). Moreover, the interaction between TV and HPV infection was insensitive to the deletion of some studies and correlation coefficients, consequently, the results were robust and reliable. These results suggested that TV is positively associated with HPV infection, and HPV is also a risk factor for TV infection.